Legal Negotiation Skills Training for Dispute Resolution - Montayana Meher; Agata Kurniati; Rosmalinda Rosmalinda (Abdimas Indonesian Journal, 2026)
Dispute resolution through non-litigation mechanisms has increasingly developed as an alternative approach that is faster, more efficient, and oriented toward achieving mutual agreement between the parties. However, legal negotiation skills remain a competency that is not yet optimally mastered by law students, as the learning process tends to emphasize theoretical aspects rather than practical application. This community service program aims to enhance students’ knowledge and skills in applying legal negotiation techniques as one of the methods of out-of-court dispute resolution. The implementation method includes participant needs identification, material delivery, interactive discussions, case-based negotiation simulations, and evaluation through pre-test and post-test assessments. The participants consisted of 50 Faculty of Law students who actively participated in the training activities. The results show an improvement in participants’ understanding of the concept of legal negotiation, negotiation stages, persuasive communication techniques, negotiation strategy development, and interest-based dispute resolution (interest-based negotiation). The case simulations also enhanced participants’ ability to identify the legal positions of the parties, build effective communication, and produce mutually beneficial agreements. This program contributes to strengthening students’ practical competencies in dealing with dispute resolution dynamics in professional practice